Towards an Effective, Rational and Sustainable Approach for the Control of Cattle Ticks in the Neotropics - Estrada Peña, Agustín (2019)
Ticks and transmitted pathogens constitute a major burden for cattle industry in the Neotropics. To address this limitation, the Spanish Ibero-American Program of Science and Technology in Development office (CYTED) supported from 2018 a network of scientists named “LaGar” (CYTED code 118RT0542) aimed at optimizing the control strategies of cattle ticks in the neotropical region. As part of network activities, a meeting and course were organized on 4–8 November 2019 in Querétaro, Mexico to address the objective of developing the infrastructure necessary for an effective, sustainable (i.e., combination of efficacious acaricides with anti-tick vaccines) and rational (i.e., considering tick ecology, seasonal dynamics and cattle-wildlife interactions) control of cattle tick infestations and transmitted pathogens. The course was focused on scientists, students, cattle holders and producers and pharmaceutical/industry representatives. In this way the course addressed the different views presented by participants with the conclusion of producing a research-driven combination of different interventions for the control of tick tick-borne diseases.